Determination of Vitamin B6 (pyridoxine hydrochloride) in Pharmaceutical Preparations Using High Performance Liquid Chromatography - Mahmood, Hana Sh.; Ahmad, Rabah R. (Iraqi Journal of Science, 2019)
Determination of vitamin B6 (pyridoxine hydrochloride) was described using high performance liquid chromatographic method. The analysis was achieved by cosmos IL 5C18-MS-II column (250 mm x 4.6 mm i. d., 5µm particle size) at room temperature. The mobile phase used was Acetonitrile, buffer solution (Citric acid, Na2HPO4 pH4) buffer solution in the ratio (70:30) (V: V). the flow rate was set to 1.25 mL.min-1 and the retention time 1.82 min with UV-detection at 282 nm. Beer's law was obeyed over the concentration range 10-1250 µg.mL-1. The method was accurate (relative error % less than 0.05%), precise (RSD better than ±1.05%), average recovery 100.05%, with a limit of detection and quantification of 2.2μg.ml−1, and 7.34μg.mL−1 respectively. The proposed method was successfully applied to determine the pyridoxine hydrochloride in pharmaceutical preparations in both forms of tablet and injection